Feminist HCI and narratives of design semantics in DIY music hardware - Jawad, Karolina; Xambó Sedó, Anna (Frontiers in Communication, 2024)
Feminist Human-Computer Interaction (HCI) integrates gender, diversity, equity, and social justice into technology research and design, fostering a more inclusive and socially aware technology landscape. This article explores the design semantics of ten Do-it-Yourself (DIY) musical instruments created by women builders. Design semantics refers to the associations conveyed by designed objects so as to identity, emotions, performance or the environment and their sensory qualities such as shape, size, touch or vision. Together these associations and qualities can establish design narratives that influence the way meaning is ascribed. We conduct an analysis of these instruments to answer the question of how fabulations of design semantics, through the lens of feminist HCI principles, can reshape our understanding of gender bias in object design within the realm of DIY musical instruments constructed by women builders. Our investigation uncovers a feminist narrative taking shape as we found out that DIY instruments design contributes to the fabulation of alternative futures that challenge prevalent current gender expectations associated with commercial music hardware. DIY instruments provide a platform for questioning established gender norms, enabling the development of technologies that embrace diverse perspectives and maintain a technical identity.